Formulação e avaliação de um bioherbicida a partir de fermentação submersa do fungo Diaporthe sp. - Almeida, Thiago Castro de (2019)
The search for new tools that help in the management of weeds can be through biomolecules in bioherbicides produced by microorganisms, capable of controlling weeds with low toxicity to the environment. Biomolecules are metabolites released during microbial growth in fermentation, being thus found in low concentration and easy degradation. In this sense, the objective of this work was to study the spray drying formulation of a bioherbicide produced in submerged fermentation of the fungus Diaporthe sp. Thus, the study of the variables agitation (rpm) and aeration (vvm) in the fermentation in a bioreactor continuously stirred tank (STR) was carried out through a planning design of the central rotational compound DCCR for the variables agitation (rpm) and aeration (vvm), evaluating the control of each treatment on germination and growth inhibition of cucumber seeds. Treatment 1 with the variables 47.5 rpm 1.9 vvm obtained better results. In the evaluation of the solid formulation in spray drying the influence of the feed rate (L.h-1 ) and air flow (L.min-1 ) of the inert ingredient was studied. In the evaluation of the solid formulation in spray drying the influence of the feed rate (L.h-1 ) and air flow (L.min-1 ) of the inert ingredient was studied. Where through a DCCR for the variables food flow and air flow, treatment 7 (0.2 L.h-1 and 2.5 L.min-1 ) showed the highest yield for the formulation. The efficiency of the spray drying formulation was evaluated through a completely randomized DIC design with the type factors (liquid and solid), presence of adjuvant (with or without) and percentage of the fermentative broth (5, 25 and 100% v/v) on the test plant lettuce (Lactuca sativa), through a tri factorial 2 x 2 x 3, plus one control without application. The percentage of phytotoxicity (%), dry mass (g) and activity of the enzymes guaiacol peroxidase (POD) and superoxide dismutase (SOD) were evaluated. The percentage of phytotoxicity (%) on the test plant lettuce (Lactuca sativa) among the studied factors showed that the best result was with the use of the spray formulation (solid), with adjuvant and 100 v/v% fermented broth. The treatment of higher percentage of phytotoxicity (%) showed high activity of the antioxidant enzymes SOD and POD. In this sense, it was observed that the biomolecules promoted oxidative stress in the plants, and when the fermented broth was used in the highest concentration of 100 v/v% biomolecules, the plants could not avoid through the antioxidant enzymes SOD and POD the degradation and lesions of the test plant lettuce. The results demonstrated that the technique for solid spray drying formulation was viable without degrading biomolecules with herbicidal action and that the fungus Diaporthe sp produced biomolecules with action.